2015
DOI: 10.1177/0310057x1504300615
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dialysis Modality on Blood Loss, Bleeding Complications and Transfusion Requirements in Critically Ill Patients with Dialysis-Dependent Acute Renal Failure

Abstract: Blood loss and bleeding complications may often be observed in critically ill patients on renal replacement therapies (RRT). Here we investigate procedural (i.e. RRT-related) and non-procedural blood loss as well as transfusion requirements in regard to the chosen mode of dialysis (i.e. intermittent haemodialysis [IHD] versus continuous veno-venous haemofiltration [CVVH]). Two hundred and fifty-two patients (122 CVVH, 159 male; aged 61.5±13.9 years) with dialysis-dependent acute renal failure were analysed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Other studies have shown different results. One study observed that baseline anemia (<120 g/L in women and <135 g/L in men) before starting CRRT for AKI was present in 83% with hemoglobin level dropping by 5% in the subsequent 7 days [17]. Another study found that new onset anemia (hemoglobin <100 g/L) during CRRT occurred in 31% [18].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown different results. One study observed that baseline anemia (<120 g/L in women and <135 g/L in men) before starting CRRT for AKI was present in 83% with hemoglobin level dropping by 5% in the subsequent 7 days [17]. Another study found that new onset anemia (hemoglobin <100 g/L) during CRRT occurred in 31% [18].…”
Section: Discussionmentioning
confidence: 99%
“…Excessive blood sampling has been discussed previously. Renal replacement therapy, and its associated anticoagulation regime and filter circuit changes, is another important cause of iatrogenic anaemia, with one study reporting a mean (SD) loss of up to 384.3 (291.7) ml over 7 days 85 . Many medications given to critically ill patients have side effects that can cause haemolysis and thrombocytopenia and impair erythropoiesis and haemostasis (Table 4).…”
Section: Introductionmentioning
confidence: 99%
“…In critically ill patients with acute kidney injury (AKI), the incidence of GI bleeding may be increased due to uremia-induced effects on platelets and coagulation cascades [4][5][6][7][8][9]. In addition, renal replacement therapy (RRT) is known to activate the coagulation cascades via contact of patient blood with foreign material and RRT often requires anticoagulation [5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In critically ill patients with acute kidney injury (AKI), the incidence of GI bleeding may be increased due to uremia-induced effects on platelets and coagulation cascades [4][5][6][7][8][9]. In addition, renal replacement therapy (RRT) is known to activate the coagulation cascades via contact of patient blood with foreign material and RRT often requires anticoagulation [5][6][7][8][9][10][11][12][13][14]. AKI is frequently observed in ICU patients and significantly affects morbidity and mortality [4,[14][15][16], and previous data comparing continuous versus intermittent RRT modalities in critically ill patients have indicated that up to 30% of adult RRT-treated general ICU patients may experience clinically important allcause bleeding episodes during ICU stay [7,17].…”
Section: Introductionmentioning
confidence: 99%